A Review on Artificial Intelligence: A Modern Approach - Jaideep Patel (AG Volumes, 2022)
In the future years or decades, “artificial intelligence” (AI) will be a fundamental part of all current software, making it a genuinely revolutionary achievement in computer science. This is both a danger and an opportunity at the same time. Both the defensive and offensive cyber operations will be benefiting from AI deployments. Innovative cyber attacks will also be developed to exploit AI technology’s specific vulnerabilities. As AI becomes more hungry for the training data, it will become even more critical that we think carefully about the security of our personal information. If this era-defining technology is to bring about universal safety and wealth, it will need careful global administration.